STUDENTS’ PERCEPTION OF IMITATION TECHNIQUE IN LEARNING PRONUNCIATION: A SURVEY STUDY OF ISLAMIC HIGH SCHOOL STUDENTS - Nawir, Muhammad Syahruddin (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
The students’ mastery in pronouncing English words depends not only on students themselves but also on the teacher as a facilitator. Therefore, it is very important for the students to practice their pronunciation using their ability to imitate their teachers’ pronunciation. Yet, it cannot be dismembered that students’ imitating ability is the only matter that can drag the students’ feet in learning pronunciation. As reaction for the issues, the researcher considered a technique that allowed the students to enjoy studying pronunciation and increase their ability in pronouncing English words immediately. In this case, the researcher desired to know the students’ perception in teaching pronunciation by using Imitation Technique. By knowing students’ perceptions, it allowed the researcher and teachers to know more about the students and how their opinion is in terms of learning pronunciation. The objective of this research was to find out the students’ perception toward the use of Imitation Technique in learning pronunciation at the second grade of SMAIT Al-Ishlah Maros. This study used descriptive quantitative research design in analyzing data. The total number of populations was 68 students that consist of three classes. Therefore, the sample was 21 students that chosen by random sampling technique. The result of this study was found that the students’ showed positive perception on Imitation Technique in learning pronunciation according to the data analysis. It shows that the mean score of the students’ perception on the use of Imitation Technique in their English learning was 80.81 which classified as Positive.